ANALISIS HARGA POKOK PRODUKSI USAHA INDUSTRI PERABOT DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2012 - DEVIANA DEVIANA; Rina Selva Johan; Riadi Armas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis research was conducted at the furniture industry business in the Kecamatan Tampan Kota Pekanbaru that produces regular romawi chair, where the usual romawi chair is a type of chair that is most in demand by consumers. The aim is to analyze the cost of goods sold (HPP) in the furniture industry business in the Kecamatan Tampan Kota Pekanbaru useful as a reference in determining the selling price and to determine the amount of profit earned per unit of effort for the furniture industry product regular romawi chair.Collecting data through interviews and documentation. Data analysis using quantitative descriptive analysis is then performed calculation of the cost of goods sold (HPP) per unit and profit per unit.The results obtained after the calculation of the cost of goods sold per unit and profit per unit, namely: the cost of goods sold per unit of each business furniture industry for product type romawi chair at the highest ordinary effort "Marsan Furniture" is Rp. 3.238.768/unit with a total production of 60 units per year. While the lowest occurred in the business "Barokah meubel" is Rp. 2.775.872/unit with a total production of 65 units per year. profit for regular romawi chair products are highest in the business "barokah meubel" is Rp. 724 128 / unit while the lowest occurred in the business "Marsan perabot" is Rp. 261 232 / unit. This is caused because the overhead pabrik cost "Barokah meubel" is smaller than the other furniture businesses, it affects the cost of goods sold "barokah meubel" that will also be small in comparison to other business furniture industry is Rp. 2.775.872/unit.Keywords: cost of goods sold, profit of units